الفاعلية الذاتية لدى طلبة قسم علوم التربية بجامعة وهران2 في ضوء بعض المتغيرات - زرزايحي, سلوى; غريب, العربي (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى الكشف عن مستوى الفاعلية الذاتية لدى طلبة قسم علوم التربية بجامعة وهران2 في ضوء متغيرات الجنس والمستوى الأكاديمي، حيث تم استخدام المنهج الوصفي، ولتحقيق أهداف الدراسة تم إعداد مقياس الفاعلية الذاتية المتكون من ثلاثة مجالات(الفاعلية الذاتية الشخصية، الفاعلية الذاتية الاجتماعية والفاعلية الذاتية الأكاديمية)، وتكونت عينة الدراسة من(105) طالبا وطالبة تم اختيارهم بالطريقة العشوائية البسيطة. وأظهرت النتائج أن مستوى الفاعلية الذاتية لدى عينة الدراسة كان متوسطا، فيما لم تظهر النتائج وجود فروق دالة إحصائيا في متوسط درجات طلبة قسم علوم التربية على مقياس الفاعلية الذاتية حسب متغيري الجنس(ذكور، إناث) أو المستوى الأكاديمي(الليسانس، الماستر)، وأوصت الدراسة بضرورة الاهتمام بالجانب الانفعالي لدى الطلبة وإعداد برامج إرشادية وتدريبية لتنمية فاعليتهم الذاتية.Abstract: The descriptive approach was used in this study to reveal the level of selfefficacy among students of the Department of Education Sciences at Oran University 2 in relation to gender and academic level variables. To achieve the study's objectives, a self-efficacy scale comprised of three domains was developed (personal self-efficacy, social self-efficacy, and academic self-efficacy). The study sample consisted of 105 male and female students who were chosen at random. The results showed that the level of self-efficacy in the study sample was average, but there were no statistically significant differences in the average scores of Department of Education Sciences students on the self-efficacy scale according to gender (males, females) or academic level (bachelor, master). The study recommended that students' emotional needs be addressed, as well as counseling and training programs designed to increase their selfefficacy.
مقال
Keywords: فاعلية ذاتية ; فاعلية ذاتية شخصية ; فاعلية ذاتية اجتماعية ; فاعلية ذاتية أكاديمية; Self-efficacy; Personal self-efficacy; Social self-efficacy; Academic selfefficacy